Application of sensitivity analysis in microscale heat transfer - Majchrzak, Ewa; Dziatkiewicz, Jolanta; Kałuża, Grażyna (Computer Assisted Methods in Engineering and Science, 2013)
In the paper, the thin metal film subjected to the ultrashort laser pulse has been analyzed. The heat conduction in the domain considered has been described by two-temperature model consisting of the system of two coupled parabolic equations determining the electron and lattice temperatures. The sensitivity analysis of electron and lattice temperatures with respect to the parameters appearing in mathematical description has been discussed. In particular, the changes of temperatures due to the changes of coupling factor G and the film thickness L have been estimated. At the stage of numerical computations in a case of basic as well as sensitivity problems solutions the explicit scheme of finite difference method has been used. In the final part of the paper the results of computations have been shown.